2016
DOI: 10.1136/annrheumdis-2016-eular.4641
|View full text |Cite
|
Sign up to set email alerts
|

SAT0216 Chest Ultrasound Signs of Interstitial Lung Disease in Systemic Sclerosis Patients: A Comparison between High Resolution Chest Computed Tomography Findings

Abstract: BackgroundInterstitial lung disease (ILD) is a typical clinical manifestation in Systemic Sclerosis (SSc). The high resolution chest computed tomography (HRCT) is the gold standard to evaluate and grade ILD. The presence of fibrotic tissue in the lung, or other structures beside the air, allows obtaining specific sonography images (such as ultrasound lung comet, higher pleural line thickness, irregular pleural margins and subpleural cysts) by chest ultrasound. In previous studies it was demonstrated that the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…10 Common findings are >3 B-lines seen per window 10 and a thickened, irregular pleural line >0.3 mm. 11 While interstitial lung disease is an umbrella term which can be suggestive of many pathologies, pleural irregularities are suggestive of fibrosis/parenchymal scarring 11 (Fig. 9).…”
Section: Simple Pleural Effusionsmentioning
confidence: 99%
“…10 Common findings are >3 B-lines seen per window 10 and a thickened, irregular pleural line >0.3 mm. 11 While interstitial lung disease is an umbrella term which can be suggestive of many pathologies, pleural irregularities are suggestive of fibrosis/parenchymal scarring 11 (Fig. 9).…”
Section: Simple Pleural Effusionsmentioning
confidence: 99%
“…Conversely, another study reported that only 15% of patients with a normal initial HRCT showed evidence of progression at 5 years [ 18 ]. When there are associated reticular abnormalities, which are a common finding in most SSc cases, short-term disease regression has been observed in only a minority of patients, and in the longer term, GGO usually progressed to overt fibrotic change [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. It is rare to see a reversal of HRCT modifications, and GGO is commonly associated with irreversible disease [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: High-resolution Computed Tomography In Ssc-ildmentioning
confidence: 99%
“…When there are associated reticular abnormalities, which are a common finding in most SSc cases, short-term disease regression has been observed in only a minority of patients, and in the longer term, GGO usually progressed to overt fibrotic change [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. It is rare to see a reversal of HRCT modifications, and GGO is commonly associated with irreversible disease [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Indeed, as an improvement in HRCT findings has been observed in only 5% of patients with GGO and nonfibrotic interstitial opacities, it is reasonable to presume that GGO may represent fibrosis in many SSc cases [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: High-resolution Computed Tomography In Ssc-ildmentioning
confidence: 99%
See 2 more Smart Citations